Farrerol prevents Angiotensin II-induced cardiac remodeling in vivo and in vitro - He, Jian; Xu, Dengyue; Wang, Lu; Yu, Xiaohong (Frontiers in Pharmacology, 2023)
Cardiovascular disease has become the primary disease that threatens human health and is considered the leading cause of death. Cardiac remodeling, which is associated with cardiovascular disease, mainly manifests as cardiac hypertrophy, fibrosis, inflammation and oxidative stress. Farrerol plays an important role in treating conditions such as inflammation, endothelial injury and tumors, and we speculated that Farrerol may also play an important role in mitigating cardiac hypertrophy and remodeling. We established a model of myocardial remodeling using angiotensin II (Ang II) with concurrent intraperitoneal injection of Farrerol as an intervention. We used cardiac ultrasound, immunohistochemistry, Immunofluorescence, Wheat Germ Agglutinin, Dihydroethidium, Western Blot, qPCR and other methods to detect the role of Farrerol in cardiac remodeling. The results showed that Farrerol inhibited Ang II-induced cardiac hypertrophy; decreased the ratio of heart weight to tibia length in mice; reduced inflammation, fibrosis, and oxidative stress; and reduced the size of cardiomyocytes in vivo. Farrerol inhibited Ang II-induced cardiomyocyte hypertrophy, levels of oxidative stress, and the proliferation and migration of fibroblast in vitro. Our results revealed that Farrerol could inhibit Ang II-induced cardiac remodeling. Farrerol may therefore be a candidate drug for the treatment of myocardial remodeling.